The impacts of urban sprawl on ecological connectivity in the Montreal Metropolitan Region. Issue 58 (April 2016) - Dupras, Jerôme; Marull, Joan; Parcerisas, Lluís; Coll, Francesc; Gonzalez, Andrew; Girard, Marc; Tello, Enric
Highlights: The effects of urban sprawl on the ecological connectivity of a metropolitan area (i.e. Montreal, PQ) are measured over a half-century period. Land-use changes have caused profound changes in landscape properties, both structurally and functionally. In 1966, around 45% of the land was connected, as opposed to only 6.5% in 2010. Abstract: Urban sprawl is a widely recognized phenomenon in many major cities worldwide and is a significant land use planning and management issue. This process has many impacts on the ecological function and structure of the landscape. In this article, we analyze the effects of urban sprawl on the ecological patterns and processes in the Montreal Metropolitan Region (MMR) between 1966 and 2010. The dispersed sprawl of low-density urban areas within the territory during this period sharply increased the fragmentation of the territory, isolating the few remaining natural spaces and decreasing their ecological connectivity and, ultimately, biodiversity. The results obtained clearly show that land-use changes that occurred in the MMR have caused profound changes in landscape properties, both structurally and functionally, and especially from 1981 to 2010. In 1966, around 45% of the land had a high or very high level of connectivity, and almost 38% in 1981. By 2010 only 6.5% of the landscape was connected and 73% of the territory possessed no or low connectivity.